(untitled) (Czech Journal of International Relations, 1967)
The aim of the publication was to summarize knowledge about the development and current state of Western European integration and at the same time present a realistic and comprehensive picture of integration groupings in economic, political and military terms. In this sense, it is the first comprehensive work on Western European integration. If we have followed the post-war development of capitalism, we can already see at first glance significant differences compared to the pre-war development. The economy of advanced capitalist countries is characterized by higher rates of growth, elimination of mass unemployment, softening of cyclical fluctuations, intensive technical progress and, last but not least, an increase in the real wages of workers. The severe economic upheavals of the 1930s, which worsened the position of the broad working class with their consequences, were not repeated in the collapsed development of capitalism. Although the above publication does not aim to clarify the specifics of the post-war economic development of advanced capitalist countries, nevertheless by analyzing the causes, developmental stages and social results of Western European integration contribute to the development of capitalism in our age.